1992
DOI: 10.1136/gut.33.10.1307
|View full text |Cite
|
Sign up to set email alerts
|

Gastric B-cell mucosa associated lymphoid tissue lymphoma: a clinicopathological study in 56 patients.

Abstract: Clinico-pathological features of 56 patients with primary gastric lymphoma were evaluated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0
3

Year Published

1995
1995
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 31 publications
0
15
0
3
Order By: Relevance
“…Montalban et al [5] found that complete remission had been achieved in 91% of patients in the low-grade group, but was substantially [4] found that patients with low-grade lymphoma had a 100% actuarial survival at 156 months, which was significantly better than that of 52% recorded for patients in the high-grade group. These researchers suggested that the prognosis of gastric lymphoma depended primarily on the histologic grade and stage, which are closely related.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Montalban et al [5] found that complete remission had been achieved in 91% of patients in the low-grade group, but was substantially [4] found that patients with low-grade lymphoma had a 100% actuarial survival at 156 months, which was significantly better than that of 52% recorded for patients in the high-grade group. These researchers suggested that the prognosis of gastric lymphoma depended primarily on the histologic grade and stage, which are closely related.…”
Section: Discussionmentioning
confidence: 93%
“…The distinctive low-grade B-cell MALT lymphoma of the stomach has been well characterized [4][5][6][7][8][9][10][12][13][14][15], but its relationship with the more commonly occurring large B-cell gastric lymphoma and the histologic classification of gastric lymphoma has not been clarified. Isaacson and Wright [3] classified primary B-cell lymphoma of MALT into low-grade and high-grade lymphomas with or without evidence of a lowgrade component.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations